Answer:
True
Step-by-step explanation:
Answer:
-f(3x - 1) + 2 = -18x² + 12x + 1
Step-by-step explanation:
Step 1: Find f(3x - 1)
f(3x - 1) = 2(3x - 1)² - 1
f(3x - 1) = 2(9x² - 6x + 1) - 1
f(3x - 1) = 18x² - 12x + 2 - 1
f(3x - 1) = 18x² - 12x + 1
Step 2: Plug in f(3x - 1)
-(18x² - 12x + 1) + 2
Step 3: Evaluate
-18x² + 12x - 1 + 2
-f(3x - 1) + 2 = -18x² + 12x + 1
12.6 × 0.25 = 3.15
i hope this helps
The answer to this question is B: <span>y = 30/x. I hoped I have helped you today!</span>
You already have figured the main idea. In this case, the population is growing 1.9% a year. This word can be translated into: multiplied by 101.9% (100+1.9%). That means the P0 is 6 bill, the base is 101.9%(or 1.019) and the time is 50 years. The calculation would be:
<span>P(t)=P₀a^t
</span>P(t)=6 billion * 101.9%^50= 6 billion * <span>2.56276= 15.38 billion</span><span>
</span>